Family of spies : a World War II story of Nazi espionage, betrayal, and the secret history behind Pearl Harbor - Kuehn, Christine, 1963- (Celadon Books, 2025)
"A propulsive, never-before-told story of one family's shocking involvement as Nazi and Japanese spies during WWII and the pivotal role they played in the bombing of Pearl Harbor. It began with a call from a screenwriter, asking about a story. Your family. World War II. Nazi spies. Christine Kuehn was shocked and confused. When she asked her seventy-year-old father, Eberhard, what this could possibly be about, he stalled, deflected, demurred, and then he wept. He knew this day would come. The Kuehns, a once-prominent Berlin family, saw the rise of the Nazis as a way out of the hard times that had befallen them. When the daughter of the family, Eberhard's sister, Ruth, met Nazi leader Joseph Goebbels at a party, the two hit it off, and they had an affair. But Ruth had a secret--she was half Jewish--and Goebbels found out. Rather than having Ruth killed, Goebbels instead sent the entire Kuehn family to Hawaii, to work as spies half a world away. There, Ruth and her parents established an intricate spy operation from their home, just a few miles down the road from Pearl Harbor, shielding Eberhard from the truth. They passed secrets to the Japanese, leading to the devastating attack on Pearl Harbor. After Eberhard's father was arrested and tried for his involvement in planning the assault, Eberhard learned the harsh truth about his family and faced a decision that would change the path of the Kuehn family forever. Jumping back and forth between Christine discovering her family's secret and the untold past of the spies in Germany, Japan, and Hawaii, Family of Spies is fast-paced history at its finest, and will rewrite the narrative of December 7, 1941"-- Provided by publisher.